Effects of High Intensity Interval Training and Sprint Interval Training in Patients With Asthma: A Systematic Review - UZUNOĞLU, GAMZE ERTÜRK; Günday, Çiçek; EVRENDİLEK, HALENUR; Sağır, Kübra; Aslan, Göksen Kuran (Taylor & Francis Ltd, 2022)
Objective The aim of this study is to review the effects of high-intensity interval training (HIIT)/sprint interval training (SIT) on asthma symptoms, cardiorespiratory functions, and other variables among asthmatic patients. Data sources Randomized controlled trials published between January 2000 and January 2021 were searched in PubMed/MEDLINE, Web of Science, and Cochrane Library databases. Study selections Following pre-specified inclusion criteria, this review included 7 randomized controlled studies that compare HIIT/SIT as an intervention with any other intervention and/or control group. Results Of the included studies only four reported the chronic phase effects of the HIIT/SIT protocols. HIIT and SIT protocols applied in studies differ. HIIT improved forced expiratory volume in 1 s (FEV1) in the acute phase and maximal oxygen consumption (VO2max) in the chronic phase in the asthmatic patients (p < 0.05). Conclusion To our knowledge, our systematic review is the first study evaluating the effects of HIIT/SIT protocols on asthma patients. HIIT/SIT protocols have beneficial effects on asthma patients. In order to better understand the results of these training procedures, studies that will be designed with high methodology are needed.
Keywords: Exercise; fEV1; Vo2max